2007
DOI: 10.1080/00016340600994596
|View full text |Cite
|
Sign up to set email alerts
|

Pregnancy outcome and recurrence after conservative laparoscopic surgery for borderline ovarian tumors

Abstract: In our opinion, conservative laparoscopic treatment of borderline ovarian tumors is an appropriate and reasonable therapeutic option for young women with low-stage disease who wish to preserve their childbearing potential, because the fertility results are encouraging. Recurrence can be noted after this type of treatment, but the cases of recurrent disease can be detected with close follow-up and treated accordingly. Careful selection of candidates for this kind of treatment is, of course, necessary, and close… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
16
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 28 publications
(17 citation statements)
references
References 28 publications
1
16
0
Order By: Relevance
“…Our results are in keeping with previous studies in which recurrence rates were higher after cystectomy than after unilateral salpingo-oophorectomy (17,30,31,34,35,37,43,44). This suggests that laparoscopic cystectomy should be considered only for women with one ovary or with bilateral tumors who wish to preserve their childbearing potential.…”
Section: Resultssupporting
confidence: 94%
See 1 more Smart Citation
“…Our results are in keeping with previous studies in which recurrence rates were higher after cystectomy than after unilateral salpingo-oophorectomy (17,30,31,34,35,37,43,44). This suggests that laparoscopic cystectomy should be considered only for women with one ovary or with bilateral tumors who wish to preserve their childbearing potential.…”
Section: Resultssupporting
confidence: 94%
“…Among the three patients (7%) who developed recurrences after conservative surgery, two occurred after cystectomy and one after oophorectomy, but all the recurrences did not occur in the cases of intraoperative rupture of cyst. The histologic type of recurrences was similar to the primary tumor (37).…”
Section: Therapymentioning
confidence: 92%
“…Thus, there is an interest in minimally invasive surgical staging of BOTs. As BOTs often occur in younger women, several studies have sought to address the feasibility of this approach for BOTs [14][15][16][17][18][19]. While surgical staging is recommended for BOTs diagnosed incidentally on frozen section because of the risk of under-diagnosis of invasive EOC, there are conflicting opinions as to whether patients found to have BOTs incidentally on final pathology require a repeat operation to complete staging.…”
Section: Minimally Invasive Surgical Staging Of Borderline Ovarian Tumentioning
confidence: 97%
“…Clinically, the laparotomic approach is generally reserved for larger tumors, and the possibly easy manipulation for the mass by laparotomy may reduce the risk of tumor spilling [15,17] . Laparoscopic management is an appropriate and safe therapeutic option for young women with low-stage disease who wish to preserve their childbearing potential, because the reserved fertility are encouraging [18,19] . De et al [15] found the rate of recurrences did not differ significantly in the approaches: 14% for the laparoscopic group and 17% for the laparotomic group (P > 0.05).…”
Section: The Association Between the Treatment And Prognosismentioning
confidence: 99%